INSTRUMENTS OF THE IMPROVEMENT OF ALTERNATIVE ENERGY DEVELOPMENT: Array - and (Municipal economy of cities. Series: «Economy science», 2018)
It is established that the intense growth of a part of energy generated from alternative sources is a worldwide trend. Analyzed studies of various organizations confirm the possibility of transition from traditional energy to alternative in the long term. However, despite the fact that alternative energy is more environmentally friendly and meets the criteria for sustainable development, its growth is hampered by a number of technical and economic barriers, including the limited investment opportunities of the state budgets of developing countries especially. Therefore, the definition and effective use of tools that facilitate the attraction of investment in renewable energy is a topical issue. It is shown that in recent years the annual growth of investments into renewable power is observed. The cost of producing energy from alternative sources is higher than traditional heat generation. The exception is the cost price of solar power engineering, which approaches the traditional one and, accordingly, it accounts for the largest volumes of investments. Other directions, except for wind energy, are characterized by a decline in investment activity. It is established that exclusively market mechanisms of attraction of investments in alternative energy are limited. In order to ensure the growth of investments, it is necessary to use complex non-market instruments of stimulating investors with the help of incentive and limiting instruments. The analysis of the experience of countries that are world leaders in the production of alternative energy, has allowed to identify the most common economic and administrative tools. Incentive instruments include tax, credit and customs privileges; "green" tariffs; an obligation to prioritize or compulsory purchase of produced energy; subsidy programs. The limiting instruments include, first of all, the taxation of producers of traditional energy in favor of alternative energy. The analysis of publications and information resources has shown that attracting global investment in renewable energy occurs mainly in the form of non-cash loans, "green" bonds or grant support. The bulk of commercial bank loans goes to the development of solar and wind energy. The growth of the issue of "green" bonds, the main direction of which is the investment in alternative energy, is observed. It is determined that the main sources of financing in Ukraine are international financial organizations, commercial banks and government financing. At the same time, in Ukraine there are no legislative bases for functioning of the market of "green" bonds, however, it is planned to create in the two-year period the necessary legislative bases and conditions for its functioning. The worked out researches allows us to conclude that alternative energy is an investment attractive sector of the economy. The complexity of the development of alternative energy, due to its high cost, can be solved by the complex use of traditional market and state non-market economic and administrative tools. Also, an increase in the range of traditional ways of financing alternative energy through new ones, such as crowdfunding and solar leasing, can help to boost investment. Keywords: alternative energy, renewable energy, economic instruments, administrative instruments